Review of the First Intercultural Forum of Huasteca Universities - Danza, Grupo I.; Gómez Quinto, Rosa Guadalupe; Baizabal Vásquez, Anahid; García Vásquez, Abril; Trejo Carrillo, Ramón Miguel; González Martínez, Luis Nahúm (MAGOTZI Boletín Científico de Artes del IA, 2017)
The article is a review of the First Intercultural Forum of Huastec Universities, which brought together educational institutions from the Huasteca region. The event fostered cultural, academic, and ancestral knowledge exchange with the participation of students and academics. Topics included the preservation of cultural identity and educational challenges in indigenous communities.